In The Context Of Cognitive Brain Change, The Study Of Suicide In Adolescents Is Taken Into Consideration - ZHANG Wen; SHAHNAZ SHEIBANI; AMIYA BHAUMIK (Revista Electronica de Veterinaria, 2024)
Not only is it a significant issue for the public health in China, but it is also one of the primary causes of death among young people in the United States. There have been significant shifts in the suicide rate among adolescents, particularly among young women, as a result of the recent increase in the suicide rate in the United States. Because of this, it is of the utmost importance for them to have a complete understanding of the many reasons why young people would attempt to take their own lives. If there was a connection between the psychological and clinical risk factors for suicidal behaviour and the underlying neurologic and cognitive issues that are associated with suicidal conduct, then these variables might potentially assist medical professionals in determining the appropriate therapies to provide. According to their hypothesis of a potential explanation, changes in suicidal behaviour may be significant on several levels, including the developmental, biological (genomics, proteomics, epigenetics, and immunology) levels, as well as the psychological and clinical ones. As a result, their model provides a cohesive theory that can be used to better understand this complicated discovery. This is accomplished by merging data from several fields of suicidality and attempting to explain the relationship between clinical observations, genetic research, and neuroscience in the field of suicide research. It is essential to have a comprehensive understanding of the ways in which psychological, biological, sociobiological, and clinical risk factors interact with one another in order to develop effective strategies for preventing suicidal thoughts and suicide actions.